Bilateral trans-radial approach in stenting of occluded right axillary artery - Kedev, Sashko; Jovkovski, Aleksandar; Biljana Zafirovska (Springer Science and Business Media LLC, 2014)
With recent advancement in percutaneous endovascular interventions, angioplasty and stenting of axillary artery lesions could become the treatment of choice vs. surgical intervention owing to its lower complication and mortality rates and shorter hospital stay.We report a Caucasian female case with axillary artery chronic total occlusion (CTO) with dual etiology (atherosclerotic and radiation induced), which was successfully managed with stent angioplasty. The strategy used was right radial retrograde approach with contralateral injections from left radial catheter. Two year follow-up revealed widely patent axillary stents.